2023
DOI: 10.1021/acs.jpcc.3c01827
|View full text |Cite
|
Sign up to set email alerts
|

CuZnAl@S-1 Catalyst for the Synthesis of Higher Alcohols by CO Hydrogenation

Abstract: catalysts were prepared using a solid-phase method to prepare silicate-1 molecular sieves with Cu, Zn, and Al components encapsulated in them, and their catalytic performance for CO hydrogenation was evaluated in a fixed-bed reaction. The structural and surface properties of the catalysts were characterized using X-ray diffraction, transmission electron microscopy, N 2 physisorption, and X-ray photoelectron spectroscopy and correlated with the catalytic performance. The results showed that the use of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…62 In the following study, they also disclosed the crucial role of catalyst preparation methods in ethanol production, and further elevated the ethanol selectivity to >57% in ROH alcohols. 63–65 To further facilitate C–O bond scission and C–C coupling, the addition of transition metal/alkali–metal promoters is required for a higher ethanol selectivity. Typically, the productivity of C 2+ alcohols was doubled in the presence of a cesium (Cs) promoter due to the synergistic effect among Cs, Cu, and ZnO components for the C–C bond coupling between CHx and CHyO species.…”
Section: Catalytic Methods For Ethanol Productionmentioning
confidence: 99%
“…62 In the following study, they also disclosed the crucial role of catalyst preparation methods in ethanol production, and further elevated the ethanol selectivity to >57% in ROH alcohols. 63–65 To further facilitate C–O bond scission and C–C coupling, the addition of transition metal/alkali–metal promoters is required for a higher ethanol selectivity. Typically, the productivity of C 2+ alcohols was doubled in the presence of a cesium (Cs) promoter due to the synergistic effect among Cs, Cu, and ZnO components for the C–C bond coupling between CHx and CHyO species.…”
Section: Catalytic Methods For Ethanol Productionmentioning
confidence: 99%
“…Core−shell structured CuZnAl catalysts were also used for high alcohol synthesis. Wang and co-workers 124 prepared CuZnAl@S-1, ZnAl@S-1, CuZn@S-1, and CuAl@S-1 catalysts by a solid-phase method and investigated them for high alcohol synthesis. They found that CuZnAl nanoparticles encapsulated S-1 (CuZnAl@S-1) exhibited better catalytic performance, and the C 2+ OH/ROH and ROH selectivity reached 50.63% and 27.27%, respectively.…”
Section: Modified Methanol Synthesis Catalystsmentioning
confidence: 99%